Innovative learning from school: The Danish experience - Stenlev, Lotte; Boegeskov, Lars (Base Diseño e Innovación, 2016)
Imagine European school children designing integration activities in cooperation with local refugees, local organizations and citizens, while changing the way refugees are seen by the locals. Embraced not just as refugees, but also as fellow citizens. Imagine school teachers using sustainable design-thinking to enhance the democratic consciousness among their students. Imagine future generations of change makers able to meet society’s challenges with innovative and entrepreneurial competencies to solve them. It is ambitious, but it is possible.